2018
DOI: 10.3390/foods7030037
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Flavour of Bovine Milk and Cheese from Grass Based versus Non-Grass Based Milk Production Systems

Abstract: There has been a surge in interest in relation to differentiating dairy products derived from pasture versus confined systems. The impact of different forage types on the sensory properties of milk and cheese is complex due to the wide range of on farm and production factors that are potentially involved. The main effect of pasture diet on the sensory properties of bovine milk and cheese is increased yellow intensity correlated to β-carotene content, which is a possible biomarker for pasture derived dairy prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
147
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(176 citation statements)
references
References 95 publications
(313 reference statements)
11
147
1
2
Order By: Relevance
“…Differences in taste between milk and cheese from grass-based and other production systems have been reviewed by Kilcawley, Faulker, Clarke, O'Sullivan, and Kerry (2018). Differences in taste between milk and cheese from grass-based and other production systems have been reviewed by Kilcawley, Faulker, Clarke, O'Sullivan, and Kerry (2018).…”
Section: Enhancing Milk Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…Differences in taste between milk and cheese from grass-based and other production systems have been reviewed by Kilcawley, Faulker, Clarke, O'Sullivan, and Kerry (2018). Differences in taste between milk and cheese from grass-based and other production systems have been reviewed by Kilcawley, Faulker, Clarke, O'Sullivan, and Kerry (2018).…”
Section: Enhancing Milk Qualitymentioning
confidence: 99%
“…For animal-based food products, aspects of quality relate to taste (flavour hedonics), health (human well-being) and production method ("naturalness"). Differences in taste between milk and cheese from grass-based and other production systems have been reviewed by Kilcawley, Faulker, Clarke, O'Sullivan, and Kerry (2018). They concluded that untrained assessors, who best represent consumers, were less able to discriminate sensory differences than trained panellists and that visual and texture attributes, primarily driven by changes in fat, protein and β-carotene content, were more likely to be identified than any flavour attributes.…”
Section: Enhancing Milk Qualitymentioning
confidence: 99%
“…Therefore, the differences between groups about C16:1 level in milk could be considered as a direct consequence of the different levels of C16:0. In any case, Glasser et al (2008) observed that C18:0 had an inhibiting effect on the production of milk FA from C4:0 to C16:0, while Kilcawley, Faulkner, Clarke, O'Sallivan, and Kerry (2018) reviewed that the higher intake of n-3 PUFA, and C18:3n-3 particularly, in grazing animals can reduce the FA de novo synthesis by mammary gland.…”
Section: Fatty Acid Composition Of Milk and Cheesementioning
confidence: 99%
“…Much of the research conducted comparing wet and dry aged beef has been undertaken using assessors ([1] n = 77, [7] n = 80 -91) and the research comparing these ageing regimes to those incorporating moisture permeable bags and bone-in samples have used trained panellists [9] n = 6; [10], n = 6. Sensory Acceptance Testing is a hedonic sensory methods used to determine the degree to which products are liked and has been applied to various product including meats [11]- [17], dairy products [18]- [29], salads, [30] [31], Bakery products [32] [33] and beverages [34] [35] [36] [37] [38]. Thus the objective of the present Food and Nutrition Sciences study was to directly compare the sensory acceptability, using sensory acceptance testing, of traditional bone-in dry aging to de-boned dry aged loins and de-boned dry aged loins in moisture permeable bags (dry-ageing bag), in the same study.…”
mentioning
confidence: 99%